Functional properties of bicarbonates on physicochemical attributes of ground beef. (July 2016) - Mohan, Anand; Jaico, Tracy; Kerr, William; Singh, Rakesh
Abstract: In this study, we investigated the effects of sodium bicarbonate (NaHCO3 ), potassium bicarbonate (KHCO3 ), and NaCl, alone or in combination, on raw ground beef. Raw ground beef was mixed with NaHCO3 (5 g/kg; 10 g/kg), KHCO3 (5 g/kg; 10 g/kg), and/or NaCl (5 g/kg), and the results of the treatment(s) were compared with ground beef treated with modified food starch (20 g/kg) or potato starch (20 g/kg). Adding the bicarbonates significantly increased (p < 0.05) pH and water-holding capacity (WHC) of raw ground beef. Bicarbonates with or without salt improved the WHC more than either modified food starch or potato starch. KHCO3 with NaCl provided the best adhesive values in raw ground beef. The bicarbonates and combinations of NaCl maintained the L*- values of the ground beef during retail display storage. Our findings suggest that using bicarbonates increases the WHC by increasing the pH, resulting in raw ground beef that is more tender and adhesive. Highlights: Functional properties of bicarbonate treatment to raw ground beef were investigated. Bicarbonates enhanced ground beef pH, water-holding capacity, and moisture-content. Potassium bicarbonate improved the color, texture, and aroma stability of ground beef.